PEMANFAATAN LUMPUR LAPINDO SEBAGAI BAHAN SUBSTITUSI SEMEN DALAM PEMBUATAN BATA BETON PEJAL - Anom Wiryasa, Ngk. Made; Sudarsana, I Wayan (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009, 2009)
This paper presents a determination of compressive strength and water absorption of solid concrete block. The research objective was to determine the ideal mix composition of the concrete block where Lapindo silt was used as a cement substitution. Five types of mixes were made where Type A, B, C, D and E was (100% PC; 0% LS), (90% PC; 10% LS), (80% PC; 20% LS), (70% PC; 30% LS), and (60% PC; 40% LS) respectively. The weight ratio between Portland cement and sand was 1:8 with a water cement ratio of 0.4. The cement used in this research was Gresik Portland cement and the specimens were tested in the age of 28 days. The water absorption test results showed that the use of 24.56% of Lapindo silt as a cement substitution optimally decreased the water absorption up to 18.21% and gave a compressive strength of 71.5 kg/cm2 that is qualified as B1.This was caused by the block contained SiO2 work as a filler and CaO as a bind of the materials. The small water absorption value could also increase the durability of solid concrete block. The compressive strength and water absorption of the solid concrete block with 7,25% of Lapindo silt was 100,1 kg/cm2 (qualified as B2) and 20,72% respectively.
Keywords: solid concrete block, cement substitution material, Lapindo silt, compressive strength, water absorption.